(untitled) (BIRDEM Medical Journal, 2025)
Perineal ectopic testis is a rare congenital anomaly. It can be diagnosed with physical examination and ultrasound. An empty hemiscrotum gives rise to suspicion of the disorder of undescended testis. Examination of patient with empty scrotum should include examination of sites like perineum to look for ectopic testis. Perineal ectopic testes are prone to trauma, torsion and malignancy. Early surgery is therefore recommended. Here we present a rare case of right sided empty hemiscrotum with ipsilateral perineal swelling since birth of a toddler of 16 monthswhich was later diagnosed as right sided perineal ectopic testis. Right sided inguinal orchiopexy was performed. Gubernaculum testis was found to be fixed in the perineum. BIRDEM Med J 2025; 15(2): 83-85